Gastric stress ulcers: Experimental etiopathogenic aspects: shock - bile - acid - Pressa, Carlos; Sorondo, Martín; Parodi (h), Hernán; Maedo, Mario; Veroli, Antonio; Artigalas, Raúl; Bonaba, Roberto (Cirugía del Uruguay, 1977)
In conducting a pathogenic study of gastric stress lesions, special consideration was given to three main pathogenic factos: shock, bile and acid. To this end, a total of 28 dogs were divided into five series and one or more of the factors involved was studied in each. Evaluatiin of lesions was conducted through simple blind test procedures. In the experimental model selected, a macro a nd microscopic examination of acute gastric lesions it:i-dicated that shock is a fundamental factor. Neithe bile no,· acid are essential in determining lesion. However, the combination of these three factors, -shock + bile + acid-, results in a more frequent, extense and generalized lesional response of gastric mucosa.